Nonsurgical Endodontic Management of Two Trauma-Induced Large Periapical Lesions: A 30-Months Follow-Up Case Report Using Cone Beam Computed Tomography - Kawther BelHaj Salah; Najet Aguir Mabrouk; Saida Ziada; Souad Sahtout (Disease and Health: Research Developments Vol. 8, 2025)
Introduction: This case illustrates the healing of large trauma-induced periapical mandibular and maxillary pocket cysts in a 16-year-old female patient after a nonsurgical endodontic treatment. The dental pulp is often involved in dental trauma. It may be exposed to oral bacteria via uncomplicated or complicated crown fractures. It may also be ‘sterile-exposed’ to the periodontal ligament following the severance of the neurovascular supply to the pulp at the apical foramen in luxation injuries. These two trauma scenarios can also occur simultaneously. All of these traumatic injuries have direct impact on the health of the pulp and result in various pulp responses. Pulp necrosis and subsequent infection of the root canal system is a frequent complication. In this case, pulp infection triggers an immune response in the periapical area, resulting in periapical lesions and bone resorption. Taking into account the crucial role of the microorganisms occupying the root canal in initiating and sustaining periradicular lesions, nonsurgical root canal treatment and proper infection control should be the rule in the management of apical periodontitis. The outcome assessment of periapical lesions is based on clinical and radiographic criteria, especially Cone-Beam Computed tomography which allows refined monitoring of bone healing and reossification within the lesion, much better than 2D radiography. Conclusion: In the present case, the CBCT periapical index was used to control bone healing and concluded that the lesion is considered “healing in progress”. This case confirms that even large periapical lesions could respond favorably to a well-performed nonsurgical root canal treatment.